Psychological Capital Impacts on Safety Behavior of Contractor Workers using the SEM Method - Heppy Ridhatul Aula; Dewi Kurniasih; Farizi Rachman (The Indonesian Journal of Occupational Safety and Health, 2021)
Introduction: A steam power plant company is an electric energy production company, utilizing main energy sources such as coal, biomass, and other energies that are related to production process. This company is a big industry that operates 24 hours and have many various steps of production process. It is also supported by a variety of high-risk system equipment such as confined spaces, working at height, hot work, ergonomics, mechanics, and others. This type of work can lead to workers’ unsafe conditions and unsafe acts. One of the causes is the psychological aspects of workers, namely the lack of workers’ awareness and understanding in implementing occupational safety aspects. Workers’ psychology in this study is Psychological Capital (PsyCap) with self-efficacy, hope, optimism, and resilience dimensions. This study aims to analyze PsyCap impacts on safety behavior of contractor workers. Methods: this study was an observational analytic research using cross-sectional approach. The population was all workers in a steam power plant company in units 7&8, totalling 400 contractors. This study was conducted by distributing questionnaires to 101 respondents of contractor workers. The questionnaires consisted of items about self-efficacy, hope, optimism, and resilience dimension of PsyCap and safety compliance and safety participation dimension of safety behavior. The analysis used a Structural Equational Modeling (SEM) method and AMOS software. Results: PsyCap dimensions that impacted on safety behavior was optimism. Conclusion: optimism dimension was the factor that had the strongest impact on safety behavior especially workers’ safety compliance. Meanwhile, other PsyCap dimensions which did not have not impact on safety behavior were safety compliance and safety participation dimensions.Keywords: contractor worker, psychological capital, safety behavior, steam power plant company, structural equational modelling